DEVELOPING SPORTS CITY MANAGEMENT APPROACH WITH THE DELPHI TECHNIQUE - Chudam, Wongphat (Academic Journal of Thailand National Sports University, 2022)
This study aimed to develop and present guidelines of sports city management. The research methodology was conducted into three phases: 1. Study the elements of sport city management by investigating, studying documents and related studies, and doing in - depth interviews with the experts, 2. Step 1, collect expert opinions to create some sports city management guidelines according to the Delphi Technique process. Step 2, analyze the suitability or practicality of the sports city management guidelines, as well as check the statistics, median and range, used to analyze the data between the quartiles, 3. Check the suitability and feasibility of the implementation from the experts and the implementers doing the group discussion. The results were found that the development of guidelines for the management of sports cities that were using the Delphi technique are as follows: According to the experts, five possible aspects to be used in the politics of sports management were policy and planning, administration management, community infrastructure, and academic management. These aspects were consistent with the strategies of the Sports Authority of Thailand in managing politics in sports which stood out to be the most important of all aspects. The results of consistency analysis between the experts and the officers’ discussion in the focus group showed that they agreed in making the decisions on the possibilities about the suitable aspects in managing politics in sports; meaning that the components of sports management can be used in the future.